2014
DOI: 10.1653/024.097.0458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Diets on the Development, Mortality, Survival, Food Uptake and Fecundity ofTupiocoris cucurbitaceus(Hemiptera: Miridae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
1
2
1
Order By: Relevance
“…This fertility peak was previously found for T. cucurbitaceus preying on T. absoluta and S. cerealella eggs (Cagnotti et al, 2021). However, this result does not agree with that of Burla et al (2014) who registered the highest nymph production during the first, second and third weeks of female lifespan of T. cucurbitaceus fed on E. kuehniella eggs. We also observed that T. cucurbitaceus females laid off spring in the first 4 days of their lifespan, regardless of the diet evaluated.…”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…This fertility peak was previously found for T. cucurbitaceus preying on T. absoluta and S. cerealella eggs (Cagnotti et al, 2021). However, this result does not agree with that of Burla et al (2014) who registered the highest nymph production during the first, second and third weeks of female lifespan of T. cucurbitaceus fed on E. kuehniella eggs. We also observed that T. cucurbitaceus females laid off spring in the first 4 days of their lifespan, regardless of the diet evaluated.…”
Section: Resultscontrasting
confidence: 72%
“…More than 60 % died regardless the prey on which they had fed. This value was higher than the reported by Burla et al (2014) for the same mirid on tobacco plants after feeding on E. kuehniella eggs. Neverthless, the mortality values here registered were similar (Grenier et al, 1989;Vandekerkhove et al, 2008;Labbé et al, 2018) or higher than the recorded for other mirids fed on Artemia sp.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…(2012) este depredador tuvo un periodo de míridos de 24,3 ± 1,5 d para hembras y 23,7 ± 0,6 d para machos en ambos cultivos usando B. tabaci. De acuerdo a Burla et al (2014), el alto consumo de huevos de T. vaporariorum por parte de T. cucurbitaceus sugiere la necesidad de llevar a cabo nuevos estudios para incluir este depredador en programas de control biológico en invernaderos.…”
Section: Control Biológico En Chile De La Mosca Blanca En El Tomateunclassified